Biohydrogen Production Using Immobilized Cells of Hyperthermophilic Eubacterium Thermotoga neapolitana on Porous Glass Beads - Ngo, Tien Anh; Bui, Ha Thi Viet (Journal of Technology Innovations in Renewable Energy, 2013)
Biohydrogen fermentation using immobilized cells of Thermotoga neapolitana on porous glass beads was successfully performed in a continuously stirring anaerobic bioreactor (CSABR) system operated under the conditions of temperature 75 oC, pH 7.0 and 5.0 g/L pentose (xylose) and/or hexose (glucose). The results showed that both batch and fed-batch cultivations of the immobilized cells were effective for high-rate and high-yield H2 production compared with those from the free cells. In the batch cultivation, the H2 production rate and H2 production yield of the immobilized cells, respectively achieved the highest values of 5.64 ± 0.19 mmol-H2 L-1h-1 and 1.84 ± 0.1 mol H2/mol xylose, which were almost 1.7-fold and 1.3-fold higher than those with free cells. The maximum H2 production rate (6.91 mmol L-1 h-1) in this proposed method was 1.5-fold higher than that of free cells in the fed-batch cultivation.